HUBUNGAN DUKUNGAN SOSIAL DAN KECERDASAN EMOSIONAL TERHADAP TINGKAT STRES SISWA SMP DI JAKARTA TIMUR - Fitriyani, Fadillah Nur; Mustikasari, Mustikasari (Persatuan Perawat Nasional Indonesia (JPPNI), 2023)
ABSTRAKDukungan sosial dan kecerdasan emosional diperlukan oleh remaja agar mampu mengelola stresnya menjadi respons adaptif dan tidak berkepanjangan. Tujuan Penelitian: Penelitian ini bertujuan mengetahui hubungan dukungan sosial dan kecerdasan emosional dengan tingkat stres pada siswa SMP Negeri di Jakarta Timur. Metode: Penelitian cross sectional pada 426 siswa SMP di Jakarta Timur dengan kriteria inklusi siswa SMP Negeri di Kecamatan Ciracas dengan teknik pengambilan sampel stratified random sampling pada bulan Januari sampai April 2022. Kuesioner menggunakan Depression Anxiety Stress Scale (DASS); The Social Support Questionnaire; dan Wong and Law Emotional Intelligence Scale(WLEIS). Analisis data dengan analisis univariat dan bivariat (uji chi square). Hasil: Penelitian menunjukkan tingkat dukungan sosial dan tingkat kecerdasan emosional baik tinggi maupun rendah memiliki nilai mendekati sama; hanya 41,8% responden memiliki tingkat stres normal. Terdapat hubungan yang signifikan antara variabel dukungan sosial dengan tingkat stres (p = 0,001), dan variabel kecerdasan emosional dengan tingkat stres (p=0,013). Diskusi: Dukungan sosial yang tinggi dan kecerdasan emosional individu yang tinggi dapat menurunkan stres siswa SMP di Jakarta Timur. Kesimpulan: Temuan penelitian ini dapat membantu perawat dalam memberikan asuhan keperawatan yang sesuai dengan kebutuhan siswa sehingga siswa dapat menjadi lebih aware terhadap permasalahan yang mengganggu fisik dan psikologisnya.Kata Kunci: dukungan sosial, kecerdasan emosional, siswa SMP, tingkat stres Correlation of Social Support and Emotional Intelligence with Level of Stress Among Junior High School Students in East Jakarta ABSTRACTSocial support and emotional intelligence are essential for adolescents to manage their stress as adaptive and not prolonged responses effectively. Objective: This research aims to identify the correlation of social support and emotional intelligence with the stress level among public junior high school students in East Jakarta. Methods: A cross-sectional study was conducted on 426 junior high school students in East Jakarta with inclusion criteria of students from public junior high schools in the Ciracas Subdistrict, using stratified random sampling from January to April 2022. Questionnaires used in this research included the Depression Anxiety Stress Scale (DASS), The Social Support Questionnaire, and the Wong and Law Emotional Intelligence Scale (WLEIS). Data were analyzed using univariate and bivariate analysis (chi-square test). Results: The research revealed that high and low levels of social support and emotional intelligence had nearly equal values, with only 41.8% of respondents experiencing a normal stress level. There was a significant correlation between the variables of social support and stress levels (p=0.001) and the variables of emotional intelligence and stress levels(p=0.013). Discussion: High social support and high individual emotional intelligence can reduce stress levels among junior high school students in East Jakarta. Conclusion: The findings of this research can assist nurses in providing appropriate nursing care tailored to the needs of students, enabling them to become more aware of issues affecting their physical and psychological well-being.Keywords: emotional intelligence, junior high school students, stress levels, social support